Financial Development, Exchange Rate Fluctuations and Debt Dollarization : A Firm-Level Evidence - Kim, Minsuk (IMF Working Papers; Working Paper, 2019)
This paper examines how financial development influences the debt dollarization of nonfinancial firms in a sample of emerging market economies (EMEs). The macroeconomic channels are identified from an optimal portfolio allocation model and assessed empirically using the accounting information of nonfinancial firms from 21 EMEs during 2009-2017. The results show that financial development, measured by the private credit-to-GDP ratio, mainly reduces the influence of exchange rate volatility in determining a firm's debt currency composition, among other channels. Furthermore, the effect of exchange rate volatility becomes statistically insignificant beyond an estimated threshold credit-to-GDP ratio of 100 percent.